Conceptual framework for a cardiac surgery simulation laboratory and competency-based curriculum in Pakistan — a short innovation report - Ali Aahil Noorali; Asma Altaf Hussain Merchant; Sardar Shahmir Babar Chauhan; Mustafa Ali Khan; Anam Noor Ehsan; Mohammad Bin Pervez; Muhammad Tariq; Saulat H. Fatimi (Journal of the Pakistan Medical Association, 2022)
Simulation is a commonly utilized technique in healthcare education as it provides trainees a realistic, but safe, environment to learn a variety of skills. Trainees belonging to fields known for high stakes with low margins for error, such as cardiac surgery, can greatly benefit from simulation-based education. We propose the establishment of the first multi-tier high fidelity cardiac surgery simulation lab with a structured curriculum that will eventually provide multidisciplinary training to promising cardiac surgeons across Pakistan. The simulation lab may also be used for research, grant acquisition and patent development. Our setup will include the following levels of simulation: a simple bench model, a virtual reality simulator and a unique human performance simulator. Our multitiered approach allows for appropriate sequential trainee skill progression. Finally, we hope that our model inspires the development of similar curricula and modules for trainees belonging to other surgical fields. Continuous...